2016
DOI: 10.1513/annalsats.201510-706oc
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Lung Function Is Not Associated with Prior or Future Morbidity in Children with Sickle Cell Anemia

Abstract: The majority of children with SCA have lung function that is within the normal range. Abnormal lung function patterns were not associated with prior vasoocclusive pain or acute chest syndrome episodes, and baseline lung function patterns did not predict future vasoocclusive pain or chest syndrome episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
5
37
0
1
Order By: Relevance
“…Low FEV1/FVC is a marker of airway obstruction that affects about one in five children with SCD 13,45 . Reduction in lung growth, 46 higher hemolysis 13 and/or anemia, 47 and increased pulmonary capillary blood volume 48 may contribute to airway obstruction in SCD children.…”
Section: Discussionmentioning
confidence: 99%
“…Low FEV1/FVC is a marker of airway obstruction that affects about one in five children with SCD 13,45 . Reduction in lung growth, 46 higher hemolysis 13 and/or anemia, 47 and increased pulmonary capillary blood volume 48 may contribute to airway obstruction in SCD children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are now beginning to explore the impact of pulmonary complications on lung function for adults and children with SCA . While most children with SCA have lung function within normal limits, lung growth is significantly reduced compared to age and race‐matched controls and adulthood lung restrictive defects are commonly reported . However, few studies have prospectively evaluated the longitudinal trajectory of lung function in children with SCA.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Patel and colleagues for their interest in our recently published article about lung function patterns in children with sickle cell anemia (1). In our multicenter, prospective study, we demonstrated that the majority of children with sickle cell anemia had normal lung function.…”
mentioning
confidence: 56%